Guided Reading : Dance, Dance, Dance! - Long, Ethan (New York Holiday House, 2018)
"Horse and Buggy are best friends, but Horse likes to dance and Buggy doesnt--until Horse shows him how to get down"--
Keywords: Dance -- Juvenile fiction; Horses -- Juvenile fiction; Insects -- Juvenile fiction; Carriages and carts -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship in children -- Juvenile fiction; Dance -- Fiction; Horses -- Fiction; Insects -- Fiction; Carriages and carts -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Dance -- Fiction; Horses -- Fiction; Insects -- Fiction; Carriages and carts -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Early readers